Alzheimer’s disease and infectious agents: a comprehensive review of pathogenic mechanisms and microRNA roles - Seyyed Sam Mehdi Hosseininasab; Rasoul Ebrahimi; Shirin Yaghoobpoor; Kiarash Kazemi; Yaser Khakpour; Ramtin Hajibeygi; Ashraf Mohamadkhani; Mobina Fathi; Kimia Vakili; Arian Tavasol; Zohreh Tutunchian; Tara Fazel; et al. (Frontiers in Neuroscience)
Alzheimer’s Disease (AD) is the most prevalent type of dementia and is characterized by the presence of senile plaques and neurofibrillary tangles. There are various theories concerning the causes of AD, but the connection between viral and bacterial infections and their potential role in the pathogenesis of AD has become a fascinating area of research for the field. Various viruses such as Herpes simplex virus 1 (HSV-1), Epstein–Barr virus (EBV), Cytomegalovirus (CMV), influenza viruses, and Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), as well as bacteria such as Chlamydia pneumoniae (CP), Helicobacter pylori (HP), Porphyromonas gingivalis (P. gingivalis), Spirochetes and eukaryotic unicellular parasites (e.g., Toxoplasma gondii), have been linked to AD due to their ability to activate the immune system, induce inflammation and increase oxidative stress, thereby leading to cognitive decline and AD. In addition, microRNAs (miRNAs) might play a crucial role in the pathogenesis mechanisms of these pathogens since they are utilized to target various protein-coding genes, allowing for immune evasion, maintaining latency, and suppressing cellular signaling molecules. Also, they can regulate gene expression in human cells. This article provides an overview of the association between AD and various infectious agents, with a focus on the mechanisms by which these pathogens may be related to the pathogenesis of AD. These findings suggest important areas for further research to be explored in future studies.